Pairwise frictional profile between particles determines discontinuous shear thickening transition in non-colloidal suspensions - Comtet, Jean; Chatté, Guillaume; Niguès, Antoine; Bocquet, Lydéric; Siria, Alessandro; Colin, Annie (Nature communications, 2017)
The process by which sheared suspensions go through a dramatic change in viscosity is known as discontinuous shear thickening. Although well-characterized on the macroscale, the microscopic mechanisms at play in this transition are still poorly understood. Here, by developing new experimental procedures based on quartz-tuning fork atomic force microscopy, we measure the pairwise frictional profile between approaching pairs of polyvinyl chloride and cornstarch particles in solvent. We report a clear transition from a low-friction regime, where pairs of particles support a finite normal load, while interacting purely hydrodynamically, to a high-friction regime characterized by hard repulsive contact between the particles and sliding friction. Critically, we show that the normal stress needed to enter the frictional regime at nanoscale matches the critical stress at which shear thickening occurs for macroscopic suspensions. Our experiments bridge nano and macroscales and provide long needed demonstration of the role of frictional forces in discontinuous shear thickening. Shear thickening characterizes liquid suspensions of particles that reversibly solidify subject to stress. Here, Comtet et al . show that shear thickening occurs at the transition from lubricated contacts to frictional contacts at a single-particle level, which can be linked to the change in macroscopic rheology.